PENYULUHAN PERPAJAKAN USAHA MIKRO, KECIL DAN MENENGAH DI LINGKUNGAN RT002/02, KEBAYORAN LAMA UTARA, JAKARTA SELATAN - Sidauruk, Tagor; Simarmata, Jahormin (Jurnal Pengabdian Masyarakat Satya Widyakarya, 2023)
The objective of this Community Service activity is to improve the understanding and ability of Micro, Small, and Medium Enterprises in calculating, paying, and reporting final taxes in accordance with applicable tax regulations. The activity was conducted in the RT002/02 neighborhood of North Kebayoran Lama, Kebayoran Lama, South Jakarta, and was attended by 14 small-scale traders who operate independently. The outreach used an interactive lecture method aimed at delivering direct and practical understanding to participants. Primary data were collected through questionnaires and analyzed using a T-Test or Paired Samples Test to measure differences in participants’ understanding before and after the outreach. The results indicate a significant increase in participants' knowledge regarding their tax obligations. This shows that the outreach was effective in enhancing the tax literacy of MSME actors, improving their compliance with tax reporting requirements, and supporting the legal and administrative sustainability of their businesses in the long term.